Conflict of interests in declaring state/regional loss of tax income in Indonesia - Wara, I Nyoman; Simanjuntak, Dumaria; Sinaga, Reny Yemimalina (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2023)
Empirical and juridical gaps exist in fulfilling the element of loss in state/regional (of income) as referred to in the law in Indonesia. This study aims to address two existing issues. First, to point out the illegal practices by DJP in declaring losses to state/regional (of income) in Indonesia's taxation field. Second, to suggest or offer a legal concept regarding the competent agency's constitutional authority in declaring losses to the state/regional (of income) in Indonesia's taxation field. Two conclusions are drawn based on a normative legal study using the theory of checks and balances. First, the calculation of losses on state/regional (of income) in the field of taxation does not comply with the mandate of the constitution, namely independent, accountable, and transparent because there are no applicable tax laws and regulations to regulate procedures and experts who calculate losses on state/regional (of income) areas in the field of taxation in Indonesia. Second, because losses to the state/regional (income) in the field of taxation are part of state finances, and to align with the principle of checks and balances, the constitutional authority of the competent agency in declaring it is The Audit Board of the Republic of Indonesia (BPK). Therefore, referring to BPK's authority to declare losses in state/regional (income) in Indonesian taxation is recommended.